2011
DOI: 10.1258/jtt.2010.100318
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic videoconferencing interventions for the treatment of long-term conditions

Abstract: We conducted a systematic review of literature relating to videoconferencing in therapeutic interventions for chronic conditions. Two hundred articles were reviewed in detail, 35 of which were relevant to the study. Of these, eight were randomized controlled trials (RCTs) and the remainder were service evaluations, pilot studies and case studies. Two major themes emerged, relating specifically to videoconferencing: clinical outcomes and patient satisfaction. There were 14 studies which measured clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 54 publications
(44 reference statements)
5
67
0
9
Order By: Relevance
“…Furthermore, the close-ended responses indicated that technical issues did not affect relationships. This finding is consistent with previous research (Serwe, Hersch, Pickens, & Pancheri, 2017;Steel et al, 2011).…”
Section: Close-ended Responsessupporting
confidence: 94%
“…Furthermore, the close-ended responses indicated that technical issues did not affect relationships. This finding is consistent with previous research (Serwe, Hersch, Pickens, & Pancheri, 2017;Steel et al, 2011).…”
Section: Close-ended Responsessupporting
confidence: 94%
“…It can improve the quality of rehabilitation delivered (Hailey et al, 2011;Kairy et al, 2009;McCue et al, 2010;Rogante et al, 2010) by providing an opportunity to the therapists to evaluate the intervention previously prescribed, monitor adverse events, and patients' progress (Hailey et al, 2011;Steel et al, 2011). Moreover, through these programmes an intervention can be delivered to the number of the participants at any single time, which may not always be possible within the constraints of face-to-face treatment protocols (Hailey et al, 2011;Steel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Today, the use of telemedicine to facilitate treatment and care over distance has been investigated in almost all clinical specialties [5][6][7]. Several studies have demonstrated the feasibility of using telemedicine to provide orthopaedic consultations to patients living in remote areas [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%